1987
DOI: 10.1111/j.1365-2621.1987.tb14050.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Anhydrous Milk Fat by Superficial Carbon Dioxide

Abstract: Milk fat was fractionated with supercritical CO* (SC-CO*) into 8 fractions at temperatures of 50" and 7O"C, over a pressure range of lo&350 bar. Two fractions (Ll and 2) were liquid, 3 fractions (1 I-3) were semi-solid and 3 fractions (Sl-3) were solid at 20°C. The peak melting temperature progressively increased (9.7" to 38.3"C) from fraction Ll to S3. The concentration of short chain (C24-C34) triglycerides decreased from fraction Ll to S3 while that of long chain (C42-C54) triglycerides increased gradually.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 23 publications
(9 reference statements)
6
40
0
1
Order By: Relevance
“…In this case, the amount of short-chain TGs decreased, whereas that of the long-chain TGs increased. This observation was also reported in a previous study (Arul, Boudreau, Makhlouf, Tardif, & Sahasrabudhe, 1987). The results indicate that the variation of POP composition was significantly (p b 0.05) higher when the extraction process was performed using 5% ethanol (Fig.…”
Section: Tablesupporting
confidence: 78%
“…In this case, the amount of short-chain TGs decreased, whereas that of the long-chain TGs increased. This observation was also reported in a previous study (Arul, Boudreau, Makhlouf, Tardif, & Sahasrabudhe, 1987). The results indicate that the variation of POP composition was significantly (p b 0.05) higher when the extraction process was performed using 5% ethanol (Fig.…”
Section: Tablesupporting
confidence: 78%
“…As the pressure and temperature increased, higher densities (0.7-0.9 g/cm 3 ) of SC-CO 2 are achieved, thus the solvating power of SC-CO 2 is increased. Consequently, intermediate and higher molecular weight FAs commence migration into the supercritical phase (Arul et al, 1987). FAs composition trend found in this study was similar to that found in other researches (Hammam et al, 1991;Chen et al, 1992;Lim & Rizvi, 1995;Bhaskar et al, 1998).…”
Section: Fa Compositionsupporting
confidence: 89%
“…In a homologous series of similar nature of intermolecular forces, the cohesive energy is a function of the molecular size. Volatility of TAG, therefore, decreases with increasing their molecular weight (Arul et al, 1987). Fractionation of TAG by SC-CO 2 involves the principles of solute-solvent interaction or affinity leading to miscibility of TAG with the SC-CO 2 phase.…”
Section: Tag Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Other important applications of SFE are decaffeination of tea, flavour extraction from herbs (Saldaña et al, 1999), extraction and fractionation of fats and oils (Arul et al, 1987;Froning et al, 1998;King, 2000;Hassan et al, 2001;Norulaini et al, 2004aNorulaini et al, ,b, 2009Zaidul, 2003;Zaidul et al, 2006Zaidul et al, , 2007a, cholesterol extraction (Chao et al, 1991;Froning et al, 1998), and dealcoholisation of alcoholic beverages (Señoráns et al, 2001). On a smaller scale, the extraction of aromas in juices (Spanos et al, 1993;Vega et al, 1996;Favati et al, 1998;Ollanketo et al, 2001), extraction of colourants, refinement of fats and oils, extraction of antioxidants (Tsuda et al, 1995;Fadel et al, 1999), deacidification of oil (Robin et al, 1996;Dunford and King, 2001), and inactivation of orange juice pectin esterase also have some importance (Palmer and Ting, 1995).…”
Section: Applications Of Sfe In Food Processingmentioning
confidence: 99%